Leishmania mexicana in a central Texas cat: clinical presentation, molecular identification, sandfly vector collection and novel management. Issue 1 (March 2021) - Hopke, Kaitlin; Meyers, Alyssa; Auckland, Lisa; Hamer, Sarah; Florin, David; Diesel, Alison; Patterson, Adam
Case summary: This case report documents the clinical appearance, diagnosis and novel treatment of a central Texas cat with cutaneous leishmaniosis. The cat presented with a linear erosion on the right pinnal margin, an ulcerated exophytic nodule on the right hock and a swelling in the right nostril. Cytological and histopathological findings were consistent with leishmaniosis. PCR confirmed the presence of Leishmania mexicana, a species endemic to Texas. An epidemiological investigation was conducted by trapping sandflies from the cat's environment. Sandflies collected were identified as Lutzomyia species, known vectors of Leishmania species. Given the lack of validated medical therapies for L mexicana in cats, treatments typically prescribed for canine leishmaniosis were administered. Allopurinol achieved clinical success but was discontinued due to suspected drug-related neutropenia. Topical imiquimod also improved lesional skin but was not sustainable due to application difficulty. Oral administration of artemisinin resulted in significant clinical improvement of cutaneous lesions without reported adverse events. Nearly 8 months after the initiation of artemisinin therapy, the cat remained systemically healthy with stable lesions. Relevance and novel information: This case report demonstrates endemic feline leishmaniosis in central Texas and provides the clinician with alternative therapeutic options for medical management.